2018
DOI: 10.1186/s13256-018-1765-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of voriconazole and corneal cross-linking on Phialophora verrucosa keratitis: a case report

Abstract: BackgroundWe report a rare case of Phialophora verrucosa fungal keratitis, which required various types of treatment according to the intractable natural history of the disease.Case presentationA 51-year-old Thai man with poorly controlled diabetes received a bamboo branch injury and developed a perforated corneal lesion on his left eye. A pathological study from therapeutic penetrating keratoplasty showed fungal hyphae. This was later identified as Phialophora verrucosa by polymerase chain reaction. This orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(19 reference statements)
0
5
0
Order By: Relevance
“… 6 Taechajongjintana et al showed no response of Phialophora to amphotericin B, natamycin, or itraconazole, but susceptibility to voriconazole. 2 In contrast, Banitt et al reported no activity of voriconazole, fluconazole, or amphotericin against P. verrucosa. 21 Hirst et al only eradicated the Phialophora infection after penetrating keratoplasty due to clinical progression despite aggressive topical and systemic antifungal treatment.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“… 6 Taechajongjintana et al showed no response of Phialophora to amphotericin B, natamycin, or itraconazole, but susceptibility to voriconazole. 2 In contrast, Banitt et al reported no activity of voriconazole, fluconazole, or amphotericin against P. verrucosa. 21 Hirst et al only eradicated the Phialophora infection after penetrating keratoplasty due to clinical progression despite aggressive topical and systemic antifungal treatment.…”
Section: Discussionmentioning
confidence: 98%
“…2 A–G) . After a literature search noted promising results in treating a recalcitrant P. verrucosa keratitis infection with corneal cross-linking (CXL), 2 this was performed for our patient. Following CXL treatment (Dresden protocol), 10 there was a clinical improvement, and topical and oral antifungals were maintained.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Thakur et al (2019) used the Dresden protocol against a fungal "phaco-tunnel" infection which proved successful, but the partial success of intracameral and intrastromal antifungal injections was likely a factor, and early presentation and treatment may also have roles [65]. There are also more cases [45,[66][67][68] with success attributed to PACK-CXL, but CXL protocols were not provided.…”
Section: Fungal Keratitismentioning
confidence: 99%
“…Fungal keratitis (FK) is a corneal mycotic infection mainly caused by corneal trauma with contaminated plants or objects [ 1 , 2 ], the misuse of contact lenses [ 3 , 4 ], prolonged use of topical antibiotics or corticosteroids [ 5 ], eye surgeries [ 6 ], or the immunocompromised state of the patient [ 7 , 8 ], among others. FK is a severe disease that can lead to vision loss or even the complete loss of the eye.…”
Section: Introductionmentioning
confidence: 99%